2020
DOI: 10.1101/2020.02.21.957928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intensity and dose of neuromuscular electrical stimulation influence sensorimotor cortical excitability

Abstract: Neuromuscular electrical stimulation (NMES) of the peripheral nervous system has been largely used in the field of neurorehabilitation to decrease muscle atrophy and to restore motor function in paralyzed patients. The rehabilitative effects of NMES rely on the direct or indirect efferent effect on muscle tone and afferent volleys that induce cortical excitation. Although different neuroimaging tools suggested the capability of NMES to regulate the excitability of sensorimotor cortex and corticospinal circuits… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…However, it should be noted that this study did not include a sham condition. Insausti-Delgado et al (2021) showed that neuromuscular electrical stimulation (NMES) over the wrist extensors resulted in an event-related desynchronization of sensorimotor alpha and beta oscillations, which was influenced by stimulation intensity. During high-intensity NMES (above motor threshold) a significantly larger alpha and beta desynchronization was present than during low- and medium-intensity stimulation (below motor threshold).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that this study did not include a sham condition. Insausti-Delgado et al (2021) showed that neuromuscular electrical stimulation (NMES) over the wrist extensors resulted in an event-related desynchronization of sensorimotor alpha and beta oscillations, which was influenced by stimulation intensity. During high-intensity NMES (above motor threshold) a significantly larger alpha and beta desynchronization was present than during low- and medium-intensity stimulation (below motor threshold).…”
Section: Discussionmentioning
confidence: 99%
“…We proposed the use of a median filter, since it can eliminate high-amplitude peaks in a time-series without causing signal discontinuities (which is the main problem of blanking or interpolation). Its main limitation is that it attenuates the activity at higher frequencies (exponential attenuation between 0 Hz and the 1/ws Hz, with ws being the length of the window of the median filter) (Insausti-Delgado et al, 2020). However, this frequencydependent attenuation does not have a big impact on the sensorimotor alpha oscillations (7-first time a non-invasive closed-loop system controls the stimulation in real-time and effectively deals with these artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low signal to noise ratio and artifacts often limit EEG applications. This problem aggravates when EEG is concurrently used with electromagnetic stimulation because it can contaminate the EEG signals and impede the estimation of cortical activity (Insausti-Delgado et al, 2020).…”
Section: Electroencephalography (Eeg) Constitutes the Most Common Tecmentioning
confidence: 99%
See 1 more Smart Citation
“…As with other stimulation-based techniques—functional electrical stimulation [ 7 ], transcranial direct current stimulation [ 8 ], transcranial alternating current stimulation (tACS) [ 9 ], deep brain stimulation [ 10 ], for example—the introduction of EEG into an experiment may present a significant challenge when it comes to interpretation, owing to substantial stimulation artifacts in the recorded signal. Stimulation is often applied at intensities far exceeding the amplitudes associated with EEG.…”
Section: Introductionmentioning
confidence: 99%